Parental and Pediatricians' Perception of Need for Subspecialty Training in Pediatric Emergency Medicine for Delivering Emergency Care to Pediatric Patients - Ernest G. Leva MD, FAAP; Diane Bunn Vanarsdale MD, FAAP; Niel F. Miele MD; Anna Petrova MD, PhD, MPH (SAGE Publishing, 2017)
The quality of pediatric emergency care may depend on the competence of the emergency department physicians. It is important to know whether parents and general pediatricians associate the quality of pediatric emergency care with the pediatric emergency medicine (PEM) training of the emergency department physicians. We designed the study to determine parental and pediatricians' opinion and expectation in regard to this question. Most of the surveyed parents' and pediatricians' recognize the importance of PEM training and believed that physicians trained in PEM can provide better emergency care for children. However, 53.8% of parents, especially Spanish speaking and with Medicaid/no insurance coverage, believe that the emergency care provided for their children by general pediatricians and PEM physicians is equivalent. The results of our study could be utilized by accredited PEM planners in the creation of strategies to ensure the quality of emergency care for children population.